Decolorization and decomposition of textile wastewater using a combination of electron beam irradiation and activated sludge processes - Mohd Nasir, Norlirubayah (2010)
Treatment of industrial-organic wastewater using radiation has resulted into partial and full decompositions. This study is focused on textile wastewater. The ratio between partial and full decompositions depends on the dosage of irradiation and also the initial concentration of pollutants present. Textile wastewater contains strong color, pH, high temperature, high chemical oxygen demand (COD) concentration, high 5 day’s biochemical oxygen demand (BOD5) and high suspended solid contents. In this study, the decolorization and decomposition of textile wastewater using a combination of electron beam irradiation and activated sludge processes were investigated. The objectives of this study were to investigate the performance of a combined process of electron beam irradiation and activated sludge in decolorization and decomposition of textile wastewater which complies with Standards A and B of the Environmental Quality Act Regulation 1974 and also to investigate the influence of irradiation on the biodegradability of textile wastewater. This study involved two successive methods namely electron beam irradiation technology and activated sludge process. The electron beam irradiation was effective in reducing the pH, the COD and the color of textile wastewater, while the application of an activated sludge process was efficient in decreasing the concentrations of COD and BOD5. This study was conducted in three stages. At the primary treatment, the biodegradability ratio of influent calculated was between 0.38 and 0.4, while the value of biodegradability ratio of irradiated wastewater increased up to 0.51 and 0.55. At the secondary treatment, the average of the COD removal efficiencies of irradiated diluted and biologically treated effluents calculated were between 70% and 72%, and 88% and 90%, respectively. Meanwhile, the average values of the BOD5 removal efficiency of irradiated diluted and biologically treated effluents were stated between 60% to 62%, and 94% to 95%, respectively. The average of the color removal efficiencies were higher for biologically treated compared to irradiated diluted for the HRTs of 5 days, 3 days and 2 days. The color removal efficiency of irradiated diluted achieved were between 60% and 61%, while for irradiated wastewater, the improvement of color removal efficiency increased up to 79% and 81%. At the tertiary treatment, the application of the technology of electron beam irradiation was to enhance the reduction of the COD and the color of biologically treated effluent. The doses varied at 25 kGy, 50 kGy and 100 kGy. The average of the COD removal efficiencies at 25 kGy, 50 kGy and 100 kGy obtained were between 90% to 91%, 91% to 92%, and 92% to 94%, respectively. Meanwhile, the increase of the color removal at 25 kGy, 50 kGy and 100 kGy were achieved up to 90% to 95%, 95% to 96%, and 97% to 98%, respectively. In conclusion, the application of electron beam radiation and activated sludge processes hold the greatest application of removing pollutants, reducing the color and also on enhancing the biodegradability of textile wastewater.